Genetic Diversity and Structure of Physaria on the Kaibab Plateau: Implications for Conservation - Jer Pin Chong; Jamie Minnaert‐Grote; David N. Zaya; Mary V. Ashley; Janice Coons; Jennifer M. Ramp Neale; Brenda Molano‐Flores (Ecology and Evolution)
ABSTRACT Assessing patterns of genetic diversity within and among closely related congeners is important for evaluating the conservation status of rare plant taxa. We used nuclear microsatellite genotyping to examine the genetic relatedness among three Physaria taxa on the Kaibab Plateau in northern Arizona. Over 100 species of Physaria are recognized, and are widely distributed in Western North America. On the Kaibab Plateau several taxa occur, including Physaria arizonica and two subspecies of P. kingii, P. kingii subsp. latifolia and P. kingii subsp. kaibabensis. The latter subspecies, the Kaibab bladderpod, is rare and endemic to the Kaibab Plateau and is a potential candidate to be listed under the Endangered Species Act. Morphological characters, primarily flower color, have been used to distinguish P. kingii subsp. kaibabensis from other subspecies. Here we aim to assess its genetic diversity and differentiation as compared to congeners on and around the Kaibab Plateau. We genotyped DNA obtained from leaf samples from 463 individuals collected from 26 sites representing the three putative taxa (12 P. kingii subsp. kaibabensis, 8 P. kingii subsp. latifolia, and 6 P. arizonica). Our results showed that all samples initially identified as P. kingii subsp. latifolia and P. kingii subsp. kaibabensis on the Kaibab Plateau form a single genetic cluster that is well‐differentiated from P. kingii subsp. latifolia sampled from sites off the plateau or P. arizonica on or off the plateau. For P. kingii on the plateau, our findings do not support the previous subspecies designations based on morphological characters. While additional studies of P. kingii will further resolve taxonomic uncertainties within this species, our findings indicate that the Kaibab Plateau population is genetically diverse and genetically distinct, and federal protection is justified in light of the threats faced on the Kaibab Plateau and its limited range.